Your data, their billions : unraveling and simplifying big tech - Hoffman, Jane S., 1964- (Tantor Media, Inc., 2022)
What if somebody knew everything about you? Somebody does. That somebody is "Big Tech." Facebook, Google, Amazon, Apple, and Microsoft know more about you than you do. And they make billions of dollars by cashing in on your private data. Our personal data, which Big Tech companies get for free, is the engine that drives the unregulated, free-for-all world called the digital marketplace. These corporate giants may bring us information and entertainment, convenience and connection, but they also do a lot of harm. So, what can we do about it? This eye-opening book provides vital information that has been out of reach to those who need it most-the millions of Facebook, Google, Amazon, Apple, and Microsoft users who have come to love and depend upon these digital products. Veteran consumer advocate Jane Hoffman makes the complex world of Big Tech simple to grasp as she reveals exactly how Big Tech uses-and abuses-your personal information. And she proposes a bold blueprint for reforming these corporate behemoths. Your Data, Their Billions is a guidebook to everything at stake in our digital society, from Big Tech's overreach into our daily lives to its practices that threaten our democracy